BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PENGISIAN DAN PEMANFAATAN DATA PADA BUKU KIA OLEH BIDAN DESA DI KABUPATEN SRAGEN TAHUN 2016 - Rahayu Norma Cahyani; Yudhy Dharmawan; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Maternal and Child Health Program (MCH) aims to reduce mortality and illness in the mother and child. MCH programs implemented either by charging data on KIA book and utilize the data to improve the health of mothers and children. Sragen is the area with high MMR and IMR. Completeness and use of data on KIA book still low of less than 80%. The purpose of this research to analyze the factors related to the completeness and utilization data on KIA book by midwives in Sragen. The method used is Explanatory Research with Cross Sectional Study design. The population and the sample was 34 midwives in Sragen. The data analysis are univariate and bivariate analysis with correlation of Pearson Product Moment and Rank Spearman. Based on the results of the univariate analysis results are as follows: midwife in the age group 31-40 years (82.4%), the last village midwife educated D3 Midwifery (82.4%), middle work period (50.0%), the perception of the needs of good data (52.9%), lack of good skills (61.8%), light workload (67.6%), high motivation (52.9%), the perception of the complexity of the field of complex form (70.6%), good training (55.9%), good supervision (79.4%), an award unfavorable (58.8%), the data is incomplete (61.8%), and does not utilize data (61.8%). In bivariate analysis, seen from the p value, so concluded that there was correlation of each variable between employment, skills, workload, motivation and reward with the completeness of the data on KIA book, and there was a correlation between the completeness of the data with utilization data on KIA book by midwives. Advice given to the community health center is the implementation of the training aimed to improve motivation, skills, and a sense rewarded with data filling KIA book and command to do counseling by midwives about health education.